INOVASI TEKNOLOGI BANTU PELAYANAN SARANA MOBILITAS MAHASISWA BERKEBUTUHAN KHUSUS DI UNIVERSITAS MUHAMMADIYAH BERAU: INOVASI TEKNOLOGI BANTU PELAYANAN SARANA MOBILITAS MAHASISWA BERKEBUTUHAN KHUSUS DI UNIVERSITAS MUHAMMADIYAH BERAU - Darmono (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2021)
Innovation of technology to assist mobility facilities services for students with special needs at muhammadiyah university, Berau . The purpose of this research is to find new technological devices that students can utilize to drive safely on the highway and to promote various mobility easier for them. General vehicle modifications are required so that people with disabilities who are not affiliated with the University of Muhammadiyah Berau could indeed start making a vehicle modifications and so that the outcomes of the assistive technology innovation design can be used by all people with special needs, permitting physical limitations to be overcome and people with special needs to ride relatively long distances like normal people. The appropriate assistive technology at the University of Muhammadiyah Berau is mobility assistance for students with special needs in the form of motorbikes that may be handled by students with special needs according to their needs. However, in the future may require further preparation.